Field-evaluation of a new lateral flow assay for detection of cellular and humoral immunity against Mycobacterium leprae. - Kidist Bobosha; Elisa M Tjon Kon Fat; Susan J F van den Eeden; Yonas Bekele; Jolien J van der Ploeg-van Schip; Claudia J de Dood; Karin Dijkman; Kees L M C Franken; Louis Wilson; Abraham Aseffa; John S Spencer; Tom H M Ottenhoff; et al. (PLoS Neglected Tropical Diseases, 2014)
BACKGROUND:Field-applicable tests detecting asymptomatic Mycobacterium leprae (M. leprae) infection or predicting progression to leprosy, are urgently required. Since the outcome of M. leprae infection is determined by cellular- and humoral immunity, we aim to develop diagnostic tests detecting pro-/anti-inflammatory and regulatory cytokines as well as antibodies against M. leprae. Previously, we developed lateral flow assays (LFA) for detection of cytokines and anti-PGL-I antibodies. Here we evaluate progress of newly developed LFAs for applications in resource-poor settings. METHODS:The combined diagnostic value of IP-10, IL-10 and anti-PGL-I antibodies was tested using M. leprae-stimulated blood of leprosy patients and endemic controls (EC). For reduction of the overall test-to-result time the minimal whole blood assay time required to detect distinctive responses was investigated. To accommodate LFAs for field settings, dry-format LFAs for IP-10 and anti-PGL-I antibodies were developed allowing storage and shipment at ambient temperatures. Additionally, a multiplex LFA-format was applied for simultaneous detection of anti-PGL-I antibodies and IP-10. For improved sensitivity and quantitation upconverting phosphor (UCP) reporter technology was applied in all LFAs. RESULTS:Single and multiplex UCP-LFAs correlated well with ELISAs. The performance of dry reagent assays and portable, lightweight UCP-LF strip readers indicated excellent field-robustness. Notably, detection of IP-10 levels in stimulated samples allowed a reduction of the whole blood assay time from 24 h to 6 h. Moreover, IP-10/IL-10 ratios in unstimulated plasma differed significantly between patients and EC, indicating the feasibility to identify M. leprae infection in endemic areas. CONCLUSIONS:Dry-format UCP-LFAs are low-tech, robust assays allowing detection of relevant cytokines and antibodies in response to M. leprae in the field. The high levels of IP-10 and the required shorter whole blood assay time, render this cytokine useful to discriminate between leprosy patients and EC.